Can you hear the trees talking? ebook Discovering the hidden life of the forest. - Wohlleben, Peter (2019)
WINNER OF THE AAAS/SUBARU PRIZE FOR EXCELLENCE IN SCIENCE BOOKS BASED ON THE NEW YORK TIMES BESTSELLER THE HIDDEN LIFE OF TREES This interactive and illustrated book for kids aged 8-10 introduces the wonderful science of the forest through outdoor activities, quizzes, fun facts, photographs, and more! Discover the secret life of trees with this nature and science book for kids: Can You Hear the Trees Talking? shares the mysteries and magic of the forest with young readers, revealing what trees feel, how they communicate, and the ways trees take care of their families. The author of The Hidden Life of Trees , Peter Wohlleben, tells kids about the forest internet, aphids who keep ants as pets, nature's water filters, and more fascinating things that happen under the canopy. Featuring simple activities kids can try on their own, along with quizzes, photographs, and more, Can You Hear the Trees Talking? covers a range of amazing topics including: How trees talk to each other (hint: through the wood wide web!) Why trees are important in the city How trees make us healthy and strong How trees get sick, and how we can help them get better This engaging and visually stunning book encourages learning and fun as kids discover the wonder of the natural world outside their windows. "Lush full-color photos and pictures create an immersive experience and the layout facilitates engaged, delighted learning. ...this book may prompt frequent family visits to, and a new appreciation for, neighborhood trees and local forests." — Washington Parent